Strategi Komunikasi Dan Kolaborasi Jaringan Bisnis Dalam Mengembangkan Usaha Baru Mango Elixirs - Resya Dwi Marselina; Hafiyanti Khanifihaya; Mira Nisaulhaq; Syahrul Rivaldi Irawan; Tito Widianto (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Developing effective communication strategies and appropriate collaboration in business networks is essential for creating competitive advantages, attracting investors, and expanding business market share. This study will discuss the direct impact of these variables on new business growth and the extent to which their integration can be a determining factor in new business success. Therefore, the researcher chose the research title "Business Network Communication and Collaboration Strategy in Developing New Businesses". The object of this research is the design of the new Mango Elixirs business unit. This research was conducted with the following aims: 1) to find out what kind of communication strategy for building a business network is carried out by Mango Elixirs, 2) to find out how effective the collaboration efforts made by Mango Elixirs are to strengthen business networks, and 3) to find out the communication strategy and collaboration can develop a new mango elixirs business.